2017
DOI: 10.1016/j.egypro.2017.07.409
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Anidolic Integrated Ceiling effects in interior daylight quality under real sky conditions

Abstract: The goal of this research is to demonstrate, according to subjective and objective evaluations, that a passive Anidolic Integrated Ceiling (AIC) is able to provide an adequate illumination level for optimal visual and task performance in deeper office spaces and to prove its effectiveness in enhancing interior daylighting quality. A quantitative study was performed by calculating the D.GI.P from spherical images in an office room, while a qualitative evaluation was achieved by using questionnaire survey. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Kontadakis et al (2017) considered this system as an easily mounted and various shape daylight-controlling system for side-lit spaces [27]. The ADS can enhance indoor visual comfort under a high luminous sky by providing a congenial luminous environment, keeping a more homogeneous daylight distribution, and reducing discomfort glare probability [28]. The ADS does not provide indoors with excessive indirect sunlight, which causes glare and overheating under a sunny sky [11], while an integrated ADS can improve indoor luminous performance by a higher Daylight Factor (DF) and work plan illuminances (at the rear part of the room) and improve Daylight Autonomy (DA), not at the expense of visual comfort [13].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Kontadakis et al (2017) considered this system as an easily mounted and various shape daylight-controlling system for side-lit spaces [27]. The ADS can enhance indoor visual comfort under a high luminous sky by providing a congenial luminous environment, keeping a more homogeneous daylight distribution, and reducing discomfort glare probability [28]. The ADS does not provide indoors with excessive indirect sunlight, which causes glare and overheating under a sunny sky [11], while an integrated ADS can improve indoor luminous performance by a higher Daylight Factor (DF) and work plan illuminances (at the rear part of the room) and improve Daylight Autonomy (DA), not at the expense of visual comfort [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The same researchers conducted a study on a residential building using a stainless-steel reflector covered with clear glass [24]. By using a questionnaire survey, a quantitative study was performed by Daich et al (2017) for an office room in Biskra, Algeria, and reported 64.51% participants' satisfaction with daylighting [28]. Linhart and Scartezzini (2010) evaluated the effect of an ADS on the south-oriented windows of an office in Lausanne, Switzerland, which decreased lighting power density by up to 40% without a noticeable impact on visual comfort [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concentrator was simulated for the CIE overcast sky and experimentally tested in winter weather conditions in Switzerland, where authors concluded that the admission sector of anidolic collector should match the visible part of the sky [25][26][27]. Experimental results show energy-saving potential of up to 31% compared to the reference room and additionally better visual comfort, improved uniformity and less contrast, as well as better results in human performance tests (string reading test according to Hygge and Löfberg, [28]) [29][30][31]. An asymmetric hyperbolic concentrator was developed based on non-imaging optics to contribute to the non-tracking solar applications.…”
Section: Anidolic Concentratormentioning
confidence: 99%
“…Here, we notice the necessity to transport daylight beyond the daylit 'perimeter zone' to deeper areas within the building. To daylit a building's deeper areas, a daylight transport system (DTS) can be used, where, e.g., horizontal daylight tubes (or light pipes) are argued to be efficient in delivering daylight to deeper areas of multistorey buildings [1,[11][12][13][14][15]. The HLP can increase the illuminance levels of the rear part of the room, which results in better light uniformity and thus reduces the luminous contrast of the room's front and rear areas, as stated by J.-L. Scartezzini and G. Courret [16].…”
Section: Introductionmentioning
confidence: 99%